Making Sense of Oxidative Stress in Obstructive Sleep Apnea: Mediator or Distracter? - Zhang, Jing; Veasey, Sigrid (Frontiers in Neurology, 2012)
Obstructive sleep apnea is increasingly recognized as an important contributor to cognitive impairment, metabolic derangements and cardiovascular disease and mortality. Identifying the mechanisms by which this prevalent disorder influences health outcomes is now of utmost importance. As the prevalence of this disorder steadily increases, therapies are needed to prevent or reverse sleep apnea morbidities now more than ever before. Oxidative stress is implicated in cardiovascular morbidities of sleep apnea. What role oxidative stress plays in neural injury and cognitive impairments has been difficult to understand without readily accessible tissue to biopsy in persons with and without sleep apnea. An improved understanding of the role oxidative stress plays in neural injury in sleep apnea may be developed by integrating information gained examining neural tissue in animal models of sleep apnea with key features of redox biochemistry and clinical sleep apnea studies where extra-neuronal oxidative stress characterizations have been performed. Collectively, this information sets the stage for developing and testing novel therapeutic approaches to treat and prevent, not only central nervous system injury and dysfunction in sleep apnea, but also the cardiovascular and potentially metabolic conditions associated with this prevalent, disabling disorder.